2019
DOI: 10.1038/s41598-019-46466-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Spatio-Temporal Dynamics of Aedes Albopictus Dispersal to Guide Control Interventions in Case of Exotic Arboviruses in Temperate Regions

Abstract: The increasing number of exotic arbovirus cases imported in Europe and the 2017 chikungunya outbreak in central/southern Italy highlight the urgency of evidence-based outbreak management plans to predict, prevent or interrupt spreading of these arboviruses to non-endemic countries in temperate regions. We here present the results of three mark-release-recapture experiments conducted in a peri-urban area of North-East Italy to estimate the spatio-temporal dynamics of the dispersal of Aedes albopictu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…These are ∼ 1.4 km from the treated site, a distance that exceeds the typical Ae. albopictus flight range . Despite the presence of active larval sites in the study areas, no insecticide treatments (against larvae or against adult mosquitoes) were carried out before and during the experiment, in either the treated or control site.…”
Section: Methodsmentioning
confidence: 99%
“…These are ∼ 1.4 km from the treated site, a distance that exceeds the typical Ae. albopictus flight range . Despite the presence of active larval sites in the study areas, no insecticide treatments (against larvae or against adult mosquitoes) were carried out before and during the experiment, in either the treated or control site.…”
Section: Methodsmentioning
confidence: 99%
“…The context (i.e. ecological characteristics of study sites, objectives of dispersal studies) often impedes the direct comparison of mark–release–capture estimates but recent studies estimated a mean flight range of ~200 m (Marini et al., 2010, 2019). Modelling the potential range expansion of A. albopictus over time using occupancy–detection data, its natural dispersal capabilities and habitat suitability modelling revealed that both natural and human‐aided dispersal are responsible for the rapid expansion in the region of Grenoble since its first introduction in 2012 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Probabilities of occurrence values >0.65 were converted into presence values based on the ROC. We modelled the potential natural dispersal of A. albopictus using this binary projection (representing the potential occupancy), yearly presence‐only data and dispersal capabilities estimated in A. albopictus using mark–release–recapture experiments (Marini et al., 2019). This last study estimated 212 m as the mean flight range (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations